Factors associated with death among cancer patients hospitalized for COVID-19 in Mato Grosso, Brazil - Ana Paula Muraro; Ligia Regina de Oliveira; Amanda Cristina de Souza Andrade; Ana Cláudia Pereira Terças-Trettel; Lenir Vaz Guimarães; Bárbara da Silva Nalin de Souza (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2022)
ABSTRACT: Objective: To analyze the prognostic factors for death from COVID-19 among cancer patients. Methods: This is a retrospective study based on data recorded in the reporting system for COVID-19 hospitalizations in Mato Grosso. We assessed cases of cancer patients reported between April 2020 and June 2021. We calculated absolute and relative frequencies of sociodemographic variables, hospital care variables, and comorbidities, as well as mean, median, and standard deviation of age and length of stay. Odds ratios and their respective 95% confidence intervals (95%CI) - crude and adjusted - were estimated using the logistic regression model. Results: We analyzed 948 cancer patients hospitalized for COVID-19 in Mato Grosso, with a mean age of 59.7 years. The proportion of deaths was 34.5%, the mortality rate was 3.73 deaths/day (95%CI 3.35-4.16), and the median time between admission and death was 18 days. The likelihood of death was greater among patients aged 60 years or older, with chronic lung disease, who were admitted directly to intensive care units, and required mechanical ventilation at the time of admission. Patients hospitalized from April to December 2020 and January to March 2021 had a greater chance of death than those hospitalized between April and June 2021. Conclusion: The likelihood of death from COVID-19 was greater in cancer patients hospitalized before their vaccination period in the state, as well as among older individuals and those admitted in worse clinical conditions.